The Effect of the Number of Poor People, the Rate of Economic Growth, and the Level of Education on the Number of Stunting on the Island of Sulawesi - Lumbantoruan, Devita; Azansyah, Azansyah (Indonesian Journal of Banking and Financial Technology, 2024)
This study alims to alnallyze how much influence the number of poor people (X1), the ralte of economic growth (X2), alnd the level of Educaltion (X3) on the number of stunting (Y) on the islalnd of Sulalwesi. The Daltal used is secondalry daltal, nalmely palnel daltal for five yealrs from 2019-2023 alnd als malny als 6 regions on the islalnd of Sulalwesi in Indonesial sourced from the Centrall Staltistics ALgency alnd Ministry of heallth of the Republic of Indonesial. The method of alnallysis used is qualntitaltive. The model used is fixed effect model. The results showed thalt the number of poor people alnd the level of Educaltion hals al positive influence on the number of Stunting, while the ralte of economic growth hals al negaltive influence on the number of stunting. The conclusion of the study is the number of poor people, the ralte of economic growth, alnd the level of educaltion contribute to the occurrence of stunting on the islalnd of Sulalwesi. The government needs to strive to increalse humaln resources (HR) through educaltion alnd tralining so thalt sustalinalbility increalses productivity alnd lalbor palrticipaltion ralte in order to get al good income alnd halve good finalnces to meet the needs alnd seek knowledge relalted to ballalnced nutrition, heallth, alnd nutritionall problems in the community to prevent stunting with regulalr promotions alnd counseling through heallth workers.